In Vitro Embryo Culture And Regeneration Of Seeded Banana (Musa Balbisiana Cv. Changthir) (International Journal of Environmental Sciences, 2025)
Wild and seeded diploid bananas are useful resources for utilization in banana improvement programs having the traits for tolerance to various biotic and abiotic stresses. However, their regeneration, propagation and conservation face challenges due to poor germination rate of seeds and limited survivability in natural conditions. Here, we report an optimised method for the in vitro regeneration of Musa balbisiana cv. Changthir embryos using MS basal medium added with and without plant growth regulators. Zygotic embryos cultured on MS medium supplemented with 0.5 mg/L + 1.5 mg/L BAP exhibited highest percentage of germination 94.45% within 7 days follow by MS medium supplemented with 3 mg/L BAP with 84.94%. Efficient shoot induction was observed in MS 11 medium with 82.23%, while root formation was maximum in MS5 medium (0.5 mg/L NAA) with 72.22% at 21 days. Plantlet regeneration was characterised by leaf and root development, maximum in MS5 medium with average 5.67 leaves and 11.33 roots per plantlets at 48 days. These findings demonstrated a simple and reliable method of in vitro propagation of wild banana Musa balbisiana cv. Changthir, which can be applied in the conservation and banana improvement programs.